2016
DOI: 10.3390/ijerph13060579
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seasonal Variations in Airborne Particulate Matter on Asthma-Related Airway Inflammation in Mice

Abstract: This study aimed to investigate the effects of winter and spring particulate matter (PM) on airway inflammation and allergies in a mouse asthma model. PM was collected during 7–28 February 2013 (winter) and during 7–28 April 2013 (spring) in Yonago, Japan. NC/Nga mice were co-sensitized using intranasal instillation of the PMs and Dermatophagoides farinae (Df) for 5 consecutive days, and were subsequently challenged using intranasal Df at 7 days after the last sensitization. At 24 h after the challenge, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…An epidemiological study demonstrated that in winter, the outbreaks of respiratory allergy and asthma are higher than those in other seasons (Habre et al 2014). Kurai et al (2016) reported that winter PM samples from western Japan augmented respiratory allergy symptoms in mice. Takemura et al (2016) found no correlation between seasonal respiratory symptoms' variation and common allergens as pollens, house dust mites, molds, and dog or cat dander.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study demonstrated that in winter, the outbreaks of respiratory allergy and asthma are higher than those in other seasons (Habre et al 2014). Kurai et al (2016) reported that winter PM samples from western Japan augmented respiratory allergy symptoms in mice. Takemura et al (2016) found no correlation between seasonal respiratory symptoms' variation and common allergens as pollens, house dust mites, molds, and dog or cat dander.…”
Section: Introductionmentioning
confidence: 99%
“…The common method of observing PM 2.5 -induced damage to the lungs involves the administration of PM 2.5 through intranasal instillation in the form of a suspension liquid. [ 4 22 ] This type of treatment is suitable for the study of acute injury. For this method, the collection and recovery of PM 2.5 involve the use of a multisolvent filter extraction technique that combines sonication in multiple solvents accompanied by microporous membrane filtration.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. First, ambient PM is a complex mixture of various substances, and the effects of seasonal variation and regional heterogeneity on adverse health effects have been described [ 45 , 46 , 47 , 48 ]. Therefore, we should confirm the anti-inflammatory effects of tiotropium bromide by collecting ambient PM on different days and regions.…”
Section: Discussionmentioning
confidence: 99%